2021
DOI: 10.1186/s12879-021-05940-z
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-125b-5p is a promising novel plasma biomarker for alveolar echinococcosis in patients from the southern province of Qinghai

Abstract: Background Alveolar echinococcosis (AE) is caused by parasitic infection by Echinococcus multilocularis. Its diagnosis is usually based on clinical symptoms, ultrasound, and other imaging methods. MicroRNAs (miRNAs) play important roles in disease processes and can exist in a highly stable cell-free form in body fluids. It is important to identify specific, sensitive diagnostic markers for early diagnosis and evaluation of AE. In this study, we examined hsa-miR-125b-5p as a potential plasma bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…An increase of miR-1839-5p and miR-146a-5p in the primary as well as in the secondary infection mouse models suggests that these two miRs may represent potential biomarkers of AE; however, for this purpose they will need to be robustly detected and quantified in blood samples. In this respect, a recent study showed elevated miR-125b-5p levels in plasma of patients with AE [ 56 ], supporting the potential use of miRs as biomarkers of AE. Furthermore, Luis et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An increase of miR-1839-5p and miR-146a-5p in the primary as well as in the secondary infection mouse models suggests that these two miRs may represent potential biomarkers of AE; however, for this purpose they will need to be robustly detected and quantified in blood samples. In this respect, a recent study showed elevated miR-125b-5p levels in plasma of patients with AE [ 56 ], supporting the potential use of miRs as biomarkers of AE. Furthermore, Luis et al .…”
Section: Discussionmentioning
confidence: 91%
“…The miRs, isolated from human specimen, including urine, saliva, serum and tissues, are considered as biomarkers of several immune pathologies such as cancer, autoimmune diseases and viral or bacterial infections [49][50][51][52][53][54][55]. A recent study revealed miR-125b-5p to be elevated in the plasma of AE patients [56]. Furthermore, recent investigations provided evidence for a role of some miRs in the regulation of UPR signaling, with miR-181a-5p and miR-199a-5p shown to suppress the UPR master regulator GRP78 [48,57,58].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth pondering that the DLK1/Notch1 axis does not affect the activation and proliferation of naive CD4 + T cells, suggesting that there are other mechanisms affecting activation and proliferation after miR-126a-5p action. It has been found that hsa-miR-125b-5p may be a promising biomarker for early non-invasive diagnosis of alveolar echinococcosis (58). Similarly, miR-126-5p may also serve as a biomarker for early CE infection and as an auxiliary detection molecule for late imaging confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that hsa-miR-125b-5p may be a promising biomarker for early non-invasive diagnosis of alveolar echinococcosis ( 58 ). Similarly, miR-126-5p may also serve as a biomarker for early CE infection and as an auxiliary detection molecule for late imaging confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that hydatidosis can be diagnosed early and monitored through the biomarker of serum-derived egr-miR-71 [24]. The expression of hsa-miR-125b-5p was stably upregulated in the plasma and liver tissue samples from patients with alveolar echinococcosis (AE), which suggested that hsa-miR-125b-5p may be a promising biomarker for early non-invasive diagnosis of AE [45]. Serum aca-miR-146a was found to be expressed significantly higher in mice infected by Angiostrongylus cantonensis and its receiver operating characteristic (ROC) curve analysis showed that aca-miR-146a was an effective biomarker for discriminating the infected from uninfected cases with an area under the ROC curve (AUC) of 0.90.…”
Section: Discussionmentioning
confidence: 99%